Investigating educational solutions in the field of autonomous shipping at Finnish Universities - Morariu, Andrei-Raoul; Tsvetkova, Anastasia; Hellström, Magnus; Bolbot, Victor; Virtanen, Seppo (Elsevier BV, 2025)
The transformative impact of autonomous shipping requires a call for changes in the workforce and necessitates a shift in curricula. This study explores the state of higher education in Finland within the context of autonomous shipping and Maritime Autonomous Surface Ships (MASS). The research presented in this article is based on the collaboration among several educational institutions in the focal country and examines the landscape for MASS-related education and related pedagogical approaches and tools. Based on 19 interviews of educators in six Finnish universities, the article investigates predominant learning frameworks, pedagogical approaches and digital solutions while discussing the preparedness of the Finnish higher education system to address the emerging needs of the autonomous shipping domain. The findings of the presented research indicate that while a variety of digital solutions and hands-on activities, such as simulations and programming exercises, are employed, the lack of standardization across institutions poses challenges for collaboration and multi-disciplinary learning. These insights lead to a proposal of a pedagogical framework emphasizing experiential and challenge-based learning.